Biochemical changes in the inner ear fluids as the diagnostic indicator in certain hearing disorders - Asok Kumar S (Journal of All India Institute of Speech and Hearing, 1970)
The fluid system of the inner ear was formerly thought to consist of the endolymph (otic fluid) and the perilymph (periotic fluid). Recent observations have not only doubted the site of the fluid formation and absorption but have added the possibility of one more fluid system called Cortilymph. (Engstrom, 1960).